(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Two famous methods in language instruction are differentiated in this study. They are the direct technique (DM) and Grammar Translation technique (GTM). English language teachers used them widely in their classrooms. Describing the characteristics of each method, including teaching techniques, classroom practices, and their impact on language acquisition are examined in this paper. It underlines the benefits of integrating elements from each to enhance language teaching value through investigating the strengths and limitations of both methods. This paper shows real insights into the application of DM and GTM through a comparison centering on skill urgencies.